Case Report: jaundice in the young: the complexity of rare diseases beyond cholangiopathies - Simone Guglielmo; Simone Guglielmo; Francesca Pasin; Marta Biolo; Claudia Mescoli; Stefania Vio; Luca Fabris; Luca Fabris; Luca Fabris; Paolo Simioni; Paolo Simioni (Frontiers in Gastroenterology)
Jaundice is a common presentation of diseases of the biliary tree, which differential diagnosis can be challenging, in particular when associated to pancreas involvement. In this respect, autoimmune pancreatitis (AIP), a rare form of chronic pancreatitis, shares clinical presentations with pancreatic cancer, such as biliary obstruction and pancreatic mass. AIP is categorized into two subtypes, type 1, associated with elevated serum IgG4 levels and systemic involvement, including the biliary system, and type 2, which is not linked to IgG4 and can be associated with inflammatory bowel disease (IBD). Early recognition is critical as both subtypes respond well to corticosteroid therapy, potentially avoiding unnecessary surgical interventions. Here we discuss the case of a 29-year-old African man with no significant medical history, who presented with skin-scleral jaundice, pale stools, dark urine, and mild weight loss. Laboratory results showed elevated liver and pancreatic enzymes, and imaging revealed bile duct dilation and pancreatic enlargement, raising suspicion of AIP. Serum IgG4 levels were normal, and fecal calprotectin was elevated, suggesting possible IBD. Corticosteroid therapy was initiated, leading to rapid remission of jaundice. One year later, the patient developed gastrointestinal symptoms, mostly abdominal pain and diarrhea, which led to the endoscopic diagnosis of Crohn’s disease. This association further supported the diagnosis of type 2 AIP. The patient subsequently developed a recurrent jaundice due to autoimmune hemolytic anemia (AHIA), a very rare complication of AIP, supported by a positive Coombs test. Once again, corticosteroids resulted in a complete clinical response. This case illustrates the diagnostic challenges of jaundice caused by pancreato-biliary diseases and the wide range of related immunological disorders, i.e. IBD and AHIA, which may influence the clinical presentation. Prompt recognition of the disease enables us to start timely corticosteroid therapy, which confirmed the diagnosis avoiding unnecessary surgery.